Comparison of four verbal memory tests for the diagnosis and predictive value of mild cognitive impairment - Silva, Dina Lúcia Gomes da (2012)
Background: Mild cognitive impairment (MCI) is considered to be an early stage of a neurodegenerative disorder, particularly Alzheimer’s disease, and the clinical diagnosis requires the objective demonstration of cognitive deficits. The aim of the present study was to evaluate the predictive value of MCI for the conversion to dementia when using four different verbal memory tests (Logical Memory, LM; California Verbal Learning Test, CVLT; Verbal Paired-Associate Learning, VPAL; and Digit Span, DS) in the MCI criteria. Methods: Participants were consecutive patients with subjective cognitive complaints who performed a comprehensive neuropsychological evaluation and were not demented, observed in a memory clinic setting. Results: At baseline, 272 non-demented patients reporting subjective cognitive complaints were included. During the follow-up time (3.0 +- 1.9 years), 58 patients converted to dementia and 214 did not. Statistically significant differences between the converters and non-converters were present in LM, VPAL, and CVLT. A multivariate Cox regression analysis combining the four memory tests revealed that only the CVLT test remained significant as a predictor of conversion to dementia. Non-demented patients with cognitive complaints diagnosed as having MCI according to abnormal ( < 1.5 SD) learning in the CVLT test had a 3.61 higher risk of becoming demented during the follow-up. Conclusion: The verbal memory assessment using the CVLT should be preferred in the diagnostic criteria of MCI for a more accurate prediction of conversion to dementia.